Transcranial Direct-Current Stimulation (tDCS) Versus Venlafaxine ER In The Treatment Of Depression: A Randomized, Double-Blind, Single-Center Study With Open-Label, Follow-Up - Bares, Martin; Brunovsky, Martin; Stopkova, Pavla; Hejzlar, Martin; Novak, Tomas (Neuropsychiatric disease and treatment, 2019)
OBJECTIVE: Transcranial direct-current stimulation (tDCS), a relatively new neuromodulation approach, provides some evidence of an antidepressant effect. This randomized, 4-week, double-blind study with 8-week, open-label, follow-up compared the efficacy and tolerability of left anodal tDCS with venlafaxine ER (VNF) in the treatment of depression and prevention of early relapse. METHODS: Subjects (n = 57) received tDCS (2 mA, 20 sessions, 30 mins) plus placebo (n = 29) or VNF plus sham tDCS (n = 28). Responders to both interventions entered the open-label follow-up. The primary outcome was score change in the Montgomery-Åsberg Depression Rating Scale (MADRS) at week 4 of the study. Secondary outcomes were response, remission, dropout rates and relapse rates within the follow-up. UNLABELLED: The mean change in the MADRS score from baseline to week for patients treated with tDCS was 7.69 (95% CI, 5.09-10.29) points and 9.64 (95% CI, 6.20-13.09) points for patients from the VNF group, a nonsignificant difference (1.95, 95% CI -2.25-6.16; t (55) = 0.93, p= 0.36, Cohen´s d = 0.24). There were no significant between-group differences in the MADRS scores from baseline to endpoint (intention-to-treat analysis). The response/remission rate for tDCS (24%/17%) and VNF (43%/32%) as well as the dropout rate (tDCS/VNF; 6/6) did not differ significantly between groups. In the follow-up, relapse (tDCS/VNF; 1/2) and dropout (tDCS/VNF; 2/3) rates were low and comparable. LIMITATIONS: A relatively small sample size and short duration of the antidepressant treatment; no placebo arm. CONCLUSION: Overall, this study found a similar efficacy of tDCS and VNF in the acute treatment of depression and prevention of early relapse. The real clinical usefulness of tDCS and its optimal parameters in the treatment of depression should be further validated.
Keywords: tDCS; depression; transcranial direct-current stimulation; venlafaxine ER; treatment